2020
DOI: 10.1101/2020.07.12.198424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Friendly regulates membrane depolarization induced mitophagy in Arabidopsis

Abstract: The oxidative environment within the mitochondria makes them particularly vulnerable to proteotoxic stress. To maintain a healthy mitochondrial network, eukaryotes have evolved multi-tiered quality control pathways. If the stress cannot be alleviated, defective mitochondria are selectively removed by autophagy via a process termed mitophagy. Despite significant advances in metazoans and yeast, in plants, the molecular underpinnings of mitophagy are largely unknown. Here, using time-lapse imaging, electron tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Here, we observed an additive effect on the morphology and function of mitochondria in friendly atg double mutant leaves ( Figs.�8, 9 ), suggesting the independent functions of FRIENDLY and autophagy in leaves. By contrast, the study in uncoupler-treated roots indicated that FRIENDLY directly contributes to the induction of mitophagy ( Ma et al 2020 ). Therefore, the different roles of FRIENDLY in the induction of mitophagy in distinct stresses or organs should be further elucidated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Here, we observed an additive effect on the morphology and function of mitochondria in friendly atg double mutant leaves ( Figs.�8, 9 ), suggesting the independent functions of FRIENDLY and autophagy in leaves. By contrast, the study in uncoupler-treated roots indicated that FRIENDLY directly contributes to the induction of mitophagy ( Ma et al 2020 ). Therefore, the different roles of FRIENDLY in the induction of mitophagy in distinct stresses or organs should be further elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…A recent preprint article reported the contribution of mitophagy to the quality control of mitochondria in Arabidopsis roots treated with an uncoupler ( Ma et al 2020 ). Uncouplers act as proton ionophores; they dissipate the proton gradient across the mitochondrial inner membrane, resulting in the loss of ATP synthesis capacity within mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, mitophagy was shown to take place in cotyledons during de-etiolation (6h post illumination) and an analogous delay in greening capacity of atg5 was presented (Ma et al 2021), suggesting that autophagy plays a role in adjusting the number of mitochondria during photomorphogenesis and proposing cross-talk with delayed plastid biogenesis. We show here that the atg greening phenotype is not specific to atg5 and is not constitutive, but conditional on C status.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that mitochondria in friendly mutant cells formed large clusters. Interestingly, a recent study also uncovered a unique role of FRIENDLY in plant mitophagy [ 21 ]. In friendly mutants, abnormal mitophagosomes accumulated, and the level of mitophagy was significantly reduced upon mitochondrial uncoupler treatment, implying a defect in mitophagy due to the loss of FRIENDLY.…”
Section: Interplay Between Mitophagy and Mitochondrial Dynamicsmentioning
confidence: 99%
“…In germinating Arabidopsis seedlings, it has been observed that inactive mitochondria are engulfed by autophagosomes, suggesting that mitophagy facilitates the degradation of mitochondria that fail to recover from dormancy [ 20 ]. Recently, it has been also demonstrated that the de-etiolation process is suppressed in atg5 mutant plants during the transition from darkness to light [ 21 ]. In addition, intact mitochondria were observed in the vacuole of Arabidopsis under oxidative stress, implying the occurrence of mitophagy in response to stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%